La transcription du droit de la famille et de la propriété, du droit romain à la loi wisigothique - Sylvie Joye (Mélanges de la Casa de Velázquez, 2011)
The proximity of laws produced under Visigothic rule to Roman law does not make them essentially different from those of other barbarian kingdoms. Even although there is a considerable degree of apparent continuity, the elements of Roman Law included in the Breviary of Alaric and the LiberJudiciorum in fact contain profound changes. An examination of the treatment of abduction for the purpose of marriage is used here as an indicator to detect and explain what is new and what is old. What sets these two legal sources apart is essentially the skill demonstrated by their editors and compilers. These took up texts from late antiquity, juxtaposing and modifying them so as to arrive at solutions that would take account of contemporary norms of social and family behaviour, while conveying a forceful message about the role of the sovereign. All the amendments indeed bear witness to social changes and developments connected with landowning and a drive towards social hierarchy, accompanied by growing emphasis on the role of the sovereign legislator.